L and M Cone Contributions to the Midget and Parasol Ganglion Cell Receptive Fields of Macaque Monkey Retina - Diller, Lisa (J Neurosci, 2004)
Analysis of cone inputs to primate parvocellular ganglion cells suggests that red–green spectral opponency results when connections segregate input from long wavelength (L) or middle wavelength (M) sensitive cones to receptive field centers and surrounds. However, selective circuitry is not an obvious retinal feature. Rather, cone receptive field surrounds and H1 horizontal cells get mixed L and M cone input, likely indiscriminately sampled from the randomly arranged cones of the photoreceptor mosaic. Red–green spectral opponency is consistent with random connections in central retina where the mixed cone ganglion cell surround is opposed by a single cone input to the receptive field center, but not in peripheral retina where centers get multiple cone inputs. The selective and random connection hypotheses might be reconciled if cone type selective circuitry existed in inner retina. If so, the segregation of L and M cone inputs to receptive field centers and surrounds would increase from horizontal to ganglion cell, and opponency would remain strong in peripheral retina. We measured the relative strengths of L and M cone inputs to H1 horizontal cells and parasol and midget ganglion cells by recording intracellular physiological responses from morphologically identified neurons in an in vitro preparation of the macaque monkey retina. The relative strength of L and M cone inputs to H1 and ganglion cells at the same locations matched closely. Peripheral midget cells were nonopponent. These results suggest that peripheral H1 and ganglion cells inherit their L and M cone inputs from the photoreceptor mosaic unmodified by selective circuitry.